PENGUATAN CLASS ACTIONS DAN LEGAL STANDING DALAM PEMIKIRAN PERBARUAN UUPPLH DENGAN PERSPEKTIF HUKUM PROGRESIF - Nuria Siswi Enggarani (FAKULTAS HUKUM UM PAREPARE, 2019)
Increasing cases of pollution and environmental destruction are closely related to environmental law instruments as the pillars of law enforcement in the settlement of environmental disputes. Environmental law instruments are regulated by Law no. 32/2009 on Environmental Protection and Management. The type of this research is normative law research with statute approach and conceptual approach with research object that is Law no. 32 of 2009 on the Protection and Management of the Environment and various practices of class action and legal standing lawsuits. This study aims to examine the form of settlement of environmental disputes through litigation accommodated by the Environmental Law through class action (legal action) and legal standing (lawsuit of Environmental Organization). Even class action movements have been recognized in the juridical formal level, but are still constrained by the understanding of the shallow society in practical terms. Likewise, the legal standing is hampered by its own procedural petition which is considered to be limiting and reducing the space of the Environmental Organization to defend with compensation. This is the importance of the UUPPLH's renewal concept in order to better accommodate the power of community autonomy in environmental advocacy with a progressive legal perspective as a breakthrough. More concretely, the expected long-term goal of creating an upcoming environmental law reform is directed to a number of things, among others, the idea of ​​a certified judge in the field of environment, the formulation of KLH institutional strengthening and greater access placement for communities to strengthen community autonomy towards civil society